48. EVALUATION OF THE EFFECTS OF HOUTTUYNIA CORDATA (THUNB.) ON PHYSICAL SYMPTOMS IN STUDENTS WITH DAMP-HEAT CONSTITUTION ACCORDING TO TRADITIONAL MEDICINE (Vietnam Journal of Community Medicine, 2025)
Objectives: This study aimed to evaluate the effects of Houttuynia cordata (Thunb.) on physical symptoms in students with damp-heat constitution according to traditional medicine.Subjects and methods: A non-blinded Pilot pre-post intervention was conducted from February to April 2025. Thirty healthy student volunteers aged 18 and above, identified as having a damp-heat constitution by the CCMQ questionnaire and meeting inclusion and exclusion criteria, were recruited from the University of Medicine and Pharmacy at Ho Chi Minh city. Participants consumed 40 grams of fresh Houttuynia cordata leaves daily. The effectiveness was assessed by changes in the frequency and severity of typical damp-heat symptoms, using a symptom score and the NRS scale at the start, day 7, and day 15. Adverse events were monitored throughout the intervention.Results: After 7 and 15 days of intervention, both the frequency and severity of symptoms such as yellow urine, fatigue, sticky stools, bitter mouth, and abdominal distension decreased significantly (p < 0.001). After 15 days, 96.7% of students reported only mild symptoms, and no severe cases were observed. Only one case (3.33%) was recorded with moderate bloating and belching, which resolved after dose reduction; no serious adverse effects were recorded.Conclusion: A daily intake of 40 grams of fresh Houttuynia cordata effectively improved physical symptoms of damp-heat constitution in students and was safe for short-term use. Further studies with larger sample sizes and longer follow-up are needed to confirm these findings.
Keywords: Traditional medicine; damp-heat constitution; Houttuynia cordata; dietary intervention; safety.